Afterdischarges elicited by cortical electric stimulation in humans: When do they occur and what do they mean? - Gollwitzer, Stephanie; Hopfengaertner, Ruediger; Roessler, Karl; Müller, Tamara; Olmes, David Gerhard; Lang, Johannes; Koehn, Julia; Onugoren, Muejgan Dogan; Heyne, Jana; Schwab, Stefan; Hamer, Hajo (Epilepsy and Behavior, 2018)
INTRODUCTION: Afterdischarges (ADs) are a common and unwanted byproduct of direct cortical stimulation during invasive electroencephalography (EEG) recordings. Brief pulse stimulation (BPS) can sometimes terminate ADs. This study investigated AD characteristics and their relevance for emergence of stimulation seizures. In addition, AD response to BPS was analyzed. MATERIAL AND METHODS: Invasive EEG recordings including mapping with direct cortical stimulation in patients with refractory epilepsy at the Erlangen Epilepsy Center were retrospectively reviewed. Afterdischarge defined as stimulation-induced rhythmic epileptiform discharges of more than a two-second duration were analyzed regarding incidence, localization, duration, propagation pattern, morphology, and seizure emergence. In addition, the influence of AD characteristics and stimulation settings on BPS success rate was studied. RESULTS: A number of 4261 stimulation trials in 20 patients were investigated. Afterdischarge occurred in 518 trials (14.2%) and lasted 12.4 s (standard deviation [SD]: 8.6 s) on average. We elicited ADs in the seizure onset zone (SOZ) (n = 64; 19.4%), the irritative zone (n = 105, 20.0%), and outside the irritative area (n = 222, 12.5%). Rhythmic spikes (30.5%) and spike-wave complexes (30.3%) represented predominant morphologies. Afterdischarge morphology in the SOZ and hippocampus differed from other areas with polyspikes and sequential spikes being the most common types there (p = 0.0005; p < 0.0001 respectively). Hippocampal ADs were particularly frequent (n = 50, 38.2%) and long-lasting (mean: 16.6, SD: 8.3 s). Brief pulse stimulation was applied in 18.1% of the AD trials (n = 94) and was successful in 37.4% (n = 40). Success rates were highest when BPS was delivered within 9.5 s (p = 0.0048) and in ADs of spike-wave morphology (p = 0.0004). Fifteen clinical seizures emerged from ADs (3.55%), mostly evolving from sequential spikes. Afterdischarges in patients with stimulation seizures appeared more widespread (p < 0.0001) and lasted longer (mean duration 7.0 s) than in those without (mean duration 21.0 s, p = 0.0054). CONCLUSION: Afterdischarges appear in the epileptogenic and nonepileptogenic cortex. Duration and propagation patterns can help to quantify the risk of stimulation seizures, with sequential spikes being most susceptible to seizure elucidation. The hippocampus is highly sensitive to AD release. Brief pulse stimulation is a safe and efficacious way to terminate ADs, especially when delivered quickly after AD onset.
EVALuna2:34938